Erythrocyte Membrane Makeover by Plasmodium falciparum Gametocytes - Neveu, Gaëlle; Lavazec, Catherine (Frontiers in Microbiology, 2019)
Plasmodium falciparum sexual parasites, called gametocytes, are the only parasite stages responsible for transmission from humans to Anopheles mosquitoes. During their maturation, P. falciparum gametocytes remodel the structural and mechanical properties of the membrane of their erythrocyte host. This remodeling is induced by the export of several parasite proteins and a dynamic reorganization of the erythrocyte cytoskeleton. Some of these modifications are specific for sexual stages and play a key role for gametocyte maturation, sequestration in internal organs, subsequent release in the bloodstream and ability to persist in circulation. Here we discuss the mechanisms developed by gametocytes to remodel their host cell and the functional relevance of these modifications.